Epidemiology of Gastrointestinal Parasitism in Pigs in Subtropical Hill Zone of Meghalaya - LAHA, R.; DAS, M.; GOSWAMI, A.; SEN, A.; KUMAR, SURESH; KADIRVEL, G. (Indian Journal of Hill Farming, 2015)
An epidemiological study on gastrointestinal parasitic infections in pigs in a subtropical hill zone of Meghalaya was conducted from April, 2011 to March, 2012. The faecal samples of 2370 numbers of pigs were examined for the purpose and out of these, 806 (34.00%) were found positive for different gastrointestinal parasites either single or mixed infections. The mean eggs per gram of faeces (EPG) were 1244.10 with higher load of infections during rainy season. The prevalence of different gastrointestinal parasites as recorded after microscopical examination of faeces were Ascaris suum (61.29%), Strongyle spp. (45.90%), Trichuris spp. (16.25%), Strongyloides spp. (9.30%) and Eimeria spp. (37.96%). The prevalence of infection was found more in unorganized pig farms as compared to organized pig farms which were recorded as 36.18% and 28.65% with mean EPG 1345.98 and 1056.12, respectively. The infection was higher in rainy (36.96%) and cool (36.44%) seasons as compared to cold (24.75%) and warm/hot (23.12%) seasons. The coproculture of positive samples revealed the presence of larvae of Oesophagostomum dentatum (82.54 %) and Strongyloides ransomi (17.45 %).